Spiritual Intelligence, Emotional Intelligence and Contextual Performance: An Empirical Study in the Services Sector in Malaysia - Choi ling, Foo; Singh Kartar Singh, Jugindar; Arumugam, Thilageswary (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this research was to investigate the influence of spiritual intelligence and emotional intelligence towards contextual performance of employees in the services sector in Malaysia. Based on a positivist philosophy and a deductive approach, primary data was collected. This was quantitative research, and a survey method was utilized. In this study, the population were employees in the services sector and the sample size was 140 employees. Convenience sampling method was used to collect data. Self-administered were distribute through internet and by hand. Descriptive and inferential statistics were generated through the SPSS version 20 statistical tool. The multiple regression analyses showed that spiritual intelligence of employees is a slightly stronger predictor of contextual performance compared to emotional intelligence. This empirical study provides additional knowledge of the effects of spiritual intelligence and emotional intelligence to human resource managers and employees. Based on the findings, organizations can develop relevant policies and make decisions relating to recruitment and training of employees.